2019
DOI: 10.1128/jb.00069-19
|View full text |Cite
|
Sign up to set email alerts
|

Guanidine Riboswitch-Regulated Efflux Transporters Protect Bacteria against Ionic Liquid Toxicity

Abstract: Plant cell walls contain a renewable, nearly limitless supply of sugar that could be used to support microbial production of commodity chemicals and biofuels. Imidazolium ionic liquid (IIL) solvents are among the best reagents for gaining access to the sugars in this otherwise recalcitrant biomass. However, the sugars from IIL-treated biomass are inevitably contaminated with residual IILs that inhibit growth in bacteria and yeast, blocking biochemical production by these organisms. IIL toxicity is, therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…In this manner, from the literature, it was found that E. coli K-12 MG1655 also has a similar EmrE and can export imidazolium ILs. 57 However, we found that the EmrE gene of KT2440 shares only 47% identity with its E. coli homolog (Fig. S8) and one isolate (TA13_F83_I1) from an IL mix TALE experiment acquired a frame-shift mutation in its emrE, which likely disrupts its activity.…”
mentioning
confidence: 87%
“…In this manner, from the literature, it was found that E. coli K-12 MG1655 also has a similar EmrE and can export imidazolium ILs. 57 However, we found that the EmrE gene of KT2440 shares only 47% identity with its E. coli homolog (Fig. S8) and one isolate (TA13_F83_I1) from an IL mix TALE experiment acquired a frame-shift mutation in its emrE, which likely disrupts its activity.…”
mentioning
confidence: 87%
“…Perhaps with the addition of the genes known to associate with guanidine-IV riboswitches, the expanded "super-regulon" of guanidinecontrolled pathways will provide some hints at the natural source(s) of this molecule. Regardless, advances are already being made on biological processes controlled by guanidine riboswitches, 21,39,40 and guanidine aptamers appear to be promising RNA structures for use in synthetic biology. 41 It is also interesting to consider why the guanidine-IV riboswitch class was not encountered in previous bioinformatics searches for novel ncRNA motifs.…”
mentioning
confidence: 99%
“…However, guanidine is toxic to B. subtilis cells at high concentrations , and the small multi-drug resistance (SMR) transporters associated with guanidine riboswitches appear to expel guanidine to reduce its toxicity (Kermani et al 2018;Higgins et al 2019).…”
Section: Yjdf Motif Rnas: Azaaromatic Riboswitchesmentioning
confidence: 99%